Analisis Pengendalian Kualitas Biji Kopi Dengan Metode Six Sigma Pada Koperasi Baitul Qiradh (KBQ) Baburrayyan Di Kabupaten Aceh Tengah - Koko Junaidi (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2023)
Coffee is one of the leading commodities in the plantation sector. One of the districts that is the center of coffee, namely Central Aceh District, located in Aceh Province, Baitul Qiradh Cooperative (KBQ) Baburrayyan is one of the cooperatives that has succeeded in meeting international quality standards. This cooperative already has good quality but there are still a number of failures that occur so it is thirsty to be examined again. The location of this research is the Baitul Qiradh Baburrayyan Cooperative. The object that I use in this research is the chairman or manager, employees and assisted farmers at KBQ Baburrayyan. The types of data in this research are secondary and primary. The method used in this study is the six sigma method which refers to five stages, namely Define, Measure, Analyze, Improve and Control (DMAIC). The results of this study indicate that there are two causes of disability, namely the cultivation of plants by 60% and the process of sangria by 30%. This is a result of several factors, namely the purchasing and drying factors. At the measurement level, the value of DPMO is found which states that out of 1,000,000 opportunities there will be 654,982 kg of defects. At the analyze stage normal capability. At the improve stage there are four causes, namely humans, machines, methods and the environment. At the control stage, overseeing each stage. The implementation and implications for cooperatives of the latest methods greatly increase the capabilities of each stage in cooperatives. To improve quality standards, cooperatives use six sigma to run effectively and efficiently which makes the failure rate for coffee beans decrease to even zero failure.